Synergistic Effect of Biofat and Biochar of Cashew Nutshell on Mitigate Methane in the Rumen - Andi Saenab; Komang G Wiryawan; Y Retnani; Elizabeth Wina (Indonesian Center for Animal Research and Development (ICARD), 2020)
The study aimed to evaluate the effectiveness of a combination of biofat with biochar or biosmoke (bioindustrial products of cashew nut shells) at the best level as feed additive in reducing methane production and improving in vitro rumen fermentation. This experiment had two series of combination and each used a randomized block design with 6 treatments and 4 replications. A series of biofat (BF) and biochar (BC) combination were added each to substrate as followed BFBC1 = 0: 100%; BFBC2 = 25:75%; BFBC3 = 50:50%; BFBC4 = 75:25%; BFBC5 = 100: 0%. While, a series of biofat (BF) and biosmoke (BS) combination as followed BFBS1 = 0: 100%; BFBS2 = 25:75%; BFBS3 = 50:50%; BFBS4 = 75:25%; BFBS5 = 100: 0%. Both series used a control treatment which contained only substrate. The in vitro experiment was repeated 4 times and each treatment was done in duplicates. The measured variables were: total gas and CH4 productions, dry matter, organic matter, NDF degradability, NH3 and partial VFA concentrations. The results showed that the combination of biofat and biochar levels resulted in a significant decrease (P